Virulence reduction in bacteriophage resistant bacteria - León, Marcela; Bastías, Roberto (Frontiers in Microbiology, 2015)
Bacteriophages can influence the abundance, diversity and evolution of bacterial communities. Several bacteriophages have been reported to add virulence factors to their host and to increase bacterial virulence. However, lytic bacteriophages can also exert a selective pressure allowing the proliferation of strains with reduced virulence. This reduction can be explained because bacteriophages use structures present on the bacterial surface as receptors, which can be virulence factors in different bacterial species. Therefore, strains with modifications in these receptors will be resistant to bacteriophage infection and may also exhibit reduced virulence. This mini-review summarizes the reports on bacteriophage-resistant strains with reductions in virulence, and it discusses the potential consequences in phage therapy and in the use of bacteriophages to select attenuated strains for vaccines.